Facile and Green Synthesis of Iron and Silver supported Iron Nanoparticles from Novel Plant Extract of Aegle marmelos: Anti-bacterial and Anti-fungal Activity. - Munjal, Shikha; Singh, Aakash (Journal of Drug Delivery and Therapeutics, 2019)
Nanoscience and nanoparticles are getting attention in wide aspects of Chemistry, Pharmaceutical Chemistry, biotechnology medicine and even industries. The green synthesis of different single and doped metal nanoparticles has been known for last few years and having their beneficial, medicinal and pharmaceutical result. In the light of all this, we are approaching for an ecofriendly, less perilous and plant mediated green synthesis of Iron oxide nanoparticle as compared with other conventional and unsafe methods. We report for the synthesis of iron oxide NPs by aqueous extract of leaf of variety of medicinally important plant belonging from family Rutaceae and Aegle marmelos species. During the course of study different result was observed for different part of different plants, an intense surface resonance Plasmon band in the UV-visible spectrum as the basic characterization. The further study of formation of iron oxide NPs were confirmed by FTIR, SEM,EDX, TGA and XRD. Keywords: Green Synthesis, Rutaceae, A. marmelos extract, Ag-iron oxide nano particles.